WHAT IS A VIOLATION OF SHARIA PRINCIPLES OR GOVERNANCE THE CAUSE OF SHARIA BANK LIQUIDATION IN INDONESIA - Ashari, Hasan; Nugrahanti, Trinandari Prasetyo; Kaban, Reny Fitriana (International Journal of Economics, Business, and Entrepreneurship, 2022)
This study aims to explain whether violations of sharia principles or poor governance caused the failure of Islamic Rural Banks (BPRS) in Indonesia. This research was conducted by conducting interviews through questionnaires with auditors who have the competence and capability to provide information and facts that occurred in Sharia BPRs and have audited the closing balances of liquidated Sharia BPRs several times. The methodology in this research is qualitative, and the nature of this research is descriptive analysis. The results of this study conclude that there are sharia violations and governance violations in BPRS. Sharia violations are still very low concerning the failure of the BPRS due to speculation and transactions that contain an element of uncertainty (gharar). Meanwhile, the violation of governance is very strongly related to the failure of the BPRS because of the dual role of the shareholder in the management of the BPRS